The Sociolinguistics Study on the Use of Code Mixing In Gita Savitri Devi’s Youtube Channel Video - Zul Astri; Al Fian (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2020)
Sociolinguistics is a linguistic branch that studies the relationship between language and society. In this entire world, every people have their personal language style when they have interacted with other people. With the language variation that people have, they are able to mix some languages on their single utterance. When one language is mixed with the other language, in the sociolinguistics study it is called code-mixing. By applying code-mixing in social life, it has been widely used by a lot of people over the world. One Indonesian YouTuber named Gita Savitri Devi does code-mixing in some of her videos. Therefore, this research focused on code-mixing appears in Gita Savitri Devis’s YouTube channel video. This research aimed to find out the types of code-mixing that emerge in Gita Savitri Devi’s YouTube video. This research used a descriptive qualitative method and the writers are the main instrument. This research applied the documentation method in collecting the data. This research focused on analyzing the types of code-mixing of Hoffman by applying content analysis. Furthermore, the result of the types was calculated by using Sudijono formula. In this study, the writers found that there were fifty-two data in types of code-mixing. The type of intra-sentential of code-mixing was the highest type and involving a change of pronunciation was the lowest one.